Teacher Culture and Community Trust Crisis - Makmur Syukri; Amiruddin Siahaan; Uswatun Hasanah; Retno Pringadi (Universitas Pahlawan Tuanku Tambusai, 2022)
The teacher is the main symbol in education, the work culture displayed by the teacher will be an image for educational institutions. The crisis of public confidence in educational institutions is based on the quality of teaching displayed by teachers. This study seeks to describe the teacher's culture and the crisis of public trust. The type of this research is qualitative with literature study method. Sources of data and study analysis materials are quoted from credible pages of Google Scholar, DOAJ, SINTA in the form of books, scientific articles, proceedings, and final assignments (thesis, thesis, dissertation). The results of this study indicate that there has been a crisis of public confidence in the teaching culture displayed by the teacher. This is seen from the image of educational institutions that have decreased trust from the public. Likewise, external demands on teachers continue to increase to create a conducive and religious learning culture (climate). Through this research, it is hoped that it can become a scientific treasure related to creating a culture of teacher performance that can be trusted by the community.